2018
DOI: 10.18267/j.pep.663
|View full text |Cite
|
Sign up to set email alerts
|

Do Free Trade Regimes and Common Currency Drive Export Growth?

Abstract: It is believed that in many countries export activities could enhance countries' capabilities. It is also believed that trade liberalization or common currency could be an export driver. This paper examines the impact of trade liberalization and common currency on EU countries' export growth. The methodology applied in this research is constructed using specifics of the data that arise from a natural experiment. We examined how exogenous events like joining the EU, WTO, EFTA or becoming a member of Eurozone ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 48 publications
1
4
1
Order By: Relevance
“…In specific terms, 10% improvement in the level of development of trade partners led to a corresponding increase in agricultural export by 0.34%. This is inconsistent with earlier studies such as Butkus et al (2018). The results of our study indicate that replacement of continental currencies with Dollar has an insignificant effect on agricultural export.…”
Section: Empirical Results and Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…In specific terms, 10% improvement in the level of development of trade partners led to a corresponding increase in agricultural export by 0.34%. This is inconsistent with earlier studies such as Butkus et al (2018). The results of our study indicate that replacement of continental currencies with Dollar has an insignificant effect on agricultural export.…”
Section: Empirical Results and Discussioncontrasting
confidence: 99%
“…This in agreement with the view of Nin‐Pratt and Diao (2014) that implementation in regional policies beyond free trade agreement has the tendency of improving agricultural export. The result supports the finding of Butkus et al (2018) in the case of European Union countries. Finding also suggests that adopting a common currency may have minimal influence on agricultural export growth.…”
Section: Empirical Results and Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Furthermore, Frankel (2009) found that the adoption of a single currency has positive short-and long-term effects on intra-regional trade. However, Butkus et al (2018) argued that any positive effects on trade flow resulting from trade integration are only noticeable in the short term. Furthermore, Rose and Glick (2015) revisited their earlier studies from 2002, which had used pre-1998 data to estimate the effects of currency unions on trade by using conventional gravity models.…”
Section: On Common Currencies and International Tradementioning
confidence: 99%